Assessment of Antioxidant Status, Hepatic Toxicity, and Liver Histopathology in Diabetic Rats Administered Acacia polyacantha Stem Bark Extract - Tajudeen Olanrewaju Yahaya; Esther Oladele; Mutiyat Kehinde Adewale; Sa'adat Haliru; Jamilu Bala Danjuma (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Phytomedicine is increasingly incorporated into modern healthcare; however, safety concerns surrounding herbal remedies necessitate comprehensive toxicological evaluation. Acacia polyacantha is widely used in Nigerian ethnomedicine for diabetes management, yet data on its safety remain limited. This study evaluated the antioxidant capacity, hepatotoxicity, and histopathological effects of methanolic stem bark extract of A. polyacantha in alloxan-induced diabetic rats. Thirty rats were randomly assigned into six groups (n = 5): non-diabetic control, untreated diabetic control, metformin-treated diabetic rats (150 mg/kg), and diabetic rats treated with the extract at 100, 200, and 400 mg/kg body weight for 21 days. Untreated diabetic rats exhibited marked oxidative stress, characterized by reduced superoxide dismutase (46.08 ± 1.86 U/mL) and glutathione (612.40 ± 2.15 µg/mL), with elevated malondialdehyde levels (0.68 ± 0.04 µmol/L), compared with non-diabetic controls (p ? 0.05). Diabetes induction also resulted in significant hepatic dysfunction, evidenced by elevated serum aspartate aminotransferase (AST; 60.60 ± 0.69 U/L) and alanine aminotransferase (ALT; 70.11 ± 1.08 U/L), reduced albumin (7.48 ± 1.78 g/dL) and total protein (9.63 ± 2.20 g/dL), increased total bilirubin (1.41 ± 0.21 mg/dL), and vascular congestion. Treatment with A. polyacantha extract improved liver function parameters, with the most pronounced effect observed at 200 mg/kg. The medium dose (200 mg/kg) significantly normalized AST (41.26 ± 0.89 U/L) and ALT (46.13 ± 1.02 U/L), restored albumin (6.02 ± 0.25 g/dL) and total protein (12.21 ± 0.96 g/dL), and reduced bilirubin levels (1.36 ± 0.08 mg/dL), comparable to metformin-treated and non-diabetic rats (p ? 0.05). Histopathological findings corroborated the biochemical results, revealing near-normal hepatic architecture in extract-treated groups. These findings demonstrate that A. polyacantha stem bark extract exerts significant antioxidant and hepatoprotective effects, supporting its relative safety and therapeutic potential in diabetes management.